Reputation and Financial Intermediation: An Empirical Investigation of the Impact of IPO Mispricing on Underwriter Market Value - Nanda, Vikram; Yun, Youngkeol (Journal of Financial Intermediation, 1997)
This paper investigates the empirical significance of underwriter reputation capital by analyzing the impact of initial returns of IPOs on lead-underwriter market value. Consistent with reputation costs, overpriced offerings are associated with a decrease in lead-underwriter market value significantly in excess of estimated direct costs. For moderately underpriced offerings, however, underwriter wealth effects are positive. Consistent with higher reputation costs, these wealth effects are insignificant when the IPO underpricing is more extreme. In jointly managed offerings, it is lead-underwriters that are primarily affected by IPO initial performance.Journal of Economic LiteratureClassification Numbers: G24, G32.